Томас Приймак. Микола Костомаров: Біографія - Пінчук, Ю. А.; Ясь, О. В. (Український історичний журнал, 2025)
Prymak T. Mykola Kostomarov: A biography. — Toronto; Buffalo; L.: Univ. of Toronto Press, 1996. — XXIII. — 263 p.